Medicinal, Not Alternative: Regulation, Access and Safety in the Therapeutic Use of Cannabis Derivatives in Brazil - da Paixão Santana, Thais; Silva, Maria Laura; Dias Lula, Mariana; Marques Mota, Daniel; Portela, Ronaldo; Mariano Ruas, Cristina (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
This perspective article proposes a critical reflection on the regulatory, sanitary, and social challenges related to the therapeutic use of cannabis-based products in Brazil. Based on an analysis of the current regulatory framework and the implications of classifying these products outside the category of medicines, it discusses the fragility of current quality control, traceability, and pharmacovigilance mechanisms. Existing gaps, the lack of structured public policies, and the obstacles that compromise equitable access will be addressed.